Comparison of the Effectiveness of Realistic Mathematics Approach and Inquiry Approach in Improving Creative Thinking Ability and Problem-Solving Skills - Farida, Elna; Syaharuddin, Syaharuddin; Mandailina, Vera; Abdillah, Abdillah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2025)
This quantitative research examines the effectiveness of Realistic Mathematical Education (RME) and Inquiry-Based Learning approaches in enhancing students' creative thinking and problem-solving abilities. A Two two-group pretest-posttest design was used, involving 22 students in the RME group and 20 students in the Inquiry group. Data collection involved questionnaires and written tests. Descriptive analysis and independent sample t-tests were applied to analyse the data. The independent sample t-test for the questionnaire revealed a significant difference between the groups, indicating a higher score for the RME group. The findings indicate that RME is more effective in improving both creative thinking and problem-solving skills, showing smaller variations and better consistency, suggesting that RME may be a more suitable approach for teaching mathematics.